Temporal trends in hematopoietic stem cell transplantation in Argentina between 2009 and 2018: A collaborative study by GATMO-TC and INCUCAI - Basquiera, Ana Lisa (2023)
Introduction: Hematopoietic stem cell transplantation is the only curative treatment for many disorders and international data shows a growing trend. Method: We aimed to evaluate the temporal trends in HSCT transplant rates in Argentina. A time-series analysis was performed for the period 2009 to 2018 using the national database from the National Central Coordinating Institute for Ablations and Implants. Crude and standardized transplant rates were calculated. A permutation joinpoint regression model analysis was used to identify significant changes over time. Results: Altogether, 8,474 transplants were reported to INCUCAI by 28 centers (autologous 67.5%); the main indication was multiple myeloma (30%). The WHO age-sex standardized HSCT rates for the entire country were 153.3 HSCT/10 million inhabitants (95% CI 141.7–165.8) in 2009 and 260.1 HSCT/10 million inhabitants (95% CI 245.5–275.5) in 2018. There was a large gap in HSCT rates among the states and regions. The transplant rate was higher for autologous transplants throughout the years. Within the allogeneic group, the related donor transplant rate was higher than the unrelated donor transplant rate. The joinpoint regression analysis of HSCT rates for the whole country over time showed an observed annual percentage change of 6.3% (95% CI 5.4-7.3; p < 0.01). No changes were observed for unrelated donors during the study period. Conclusions: Age-sex standardized HSCT rates in Argentina are increasing, mainly due to autologous and family donor allogeneic transplants. A wide variation across the country was found, demonstrating differences in the access to transplantation among Argentine regions.